Determinants of Notification Factors for Spouses of People with HIV-AIDS (PLWHA) in Care, Support, and Treatment Services Mojokerto City - Arief Andriyanto; Arif Wicaksono (Journal of Ners and Midwifery, 2023)
A person with reactive HIV status does not always feel the need to inform their partner about their status, therefore the government is seeking a program to open their HIV status through partner notification. the application of partner notifications in reality still does not meet expectations. The aim is to analyze the determinants of notification of spouses of people with HIV-AIDS (PLWHA) in Care, Support, and Treatment Services in Mojokerto City. Research design with a cross-sectional approach. A sample of 92 PLWHA was taken based on purposive sampling. The research instrument used the partner notification checklist from the Ministry of Health of the Republic of Indonesia. Test data analysis using multiple linear regression: ANOVA. The results of the study showed that factors related to the notification of PLHIV partners include; age (0.02), education (0.02), and occupation (0.01) significantly (<0.05). it was found that the application of partner notification was poorly practiced. Some of the patient’s reasons were unwilling to provide information about their partner, feel embarrased, did not want the partner to know about their HIV-AIDS status